Grant Money with a Legal Certainty by Regional Government to Traditional Villages in Bali - I Wayan Suambara; I Nyoman Putu Budiartha (Fakultas Hukum, Universitas Warmadewa, 2023)
The regulations governing the allocation of finances for customary law community units are missing in the context of Law Number 23 of 2014 about Regional Government. Therefore, the primary objective of this study is to examine how the Regional Government can establish precise legal instructions for granting financial assistance to Traditional Villages in Bali. This investigation employs a normative method, involving a thorough analysis of Law Number 23 of 2014, Minister of Home Affairs Regulation Number 14 of 2016, and Bali Province Regional Regulation Number 4 of 2019, all related to Traditional Villages in Bali. The research findings indicate that the implementation of Minister of Home Affairs Regulation Number 14 of 2016 has not adequately ensured legal clarity. To bridge the gaps in existing norms, it is essential to reformulate both the regulations in the Law on Regional Government and the Minister of Home Affairs Regulation Number 14 of 2016. Concerning the Law on Regional Government, it's vital to amend Article 298, paragraph (5), by introducing supplementary provisions that can later be defined through Ministerial Regulations